Togeciphus Nishijima and Neoloxotaenia Sabrosky (Diptera: Chloropidae) from China - Liu, Xiaoyan; Yang, Ding (Zootaxa, 2012)
Togeciphus Nishijima and Neoloxotaenia Sabrosky are small genera in the family Chloropidae. T. truncatus sp. nov. isdescribed and N. fasciata (de Meijere) is recorded for the first time from China. Two species, T. katoi (Nishijima) and N. gracilis (de Meijere) are redescribed. Keys to the world species of the genera Togeciphus and Neoloxotaenia are presented.